2020
DOI: 10.24018/ejgeo.2020.1.5.21
|View full text |Cite
|
Sign up to set email alerts
|

Health Risk Assessment of Heavy Metals in Consumption of Vegetables Irrigated with Tin Mine Pond Water in Jos – South, Plateau State

Abstract: The water range from Pb (1.439 – 1.715), Cu (0.234 – 0.377), Cd (0.838 – 1.346), Zn (0.448 – 1.110), Cr (0.144 – 0.794), Mn (0.777 – 2.011) and As (0.584 – 1.341) mg/L.  The range in soil was Pb (67.5 – 120), Cu (8.51 – 32.5), Cd (0.21 – 1.72), Zn (70.8 – 85.6), Cr (15.8 – 29.5), Mn (14.6 – 19.1) and As (52.0 – 198) mg/kg and  in the vegetables in the range of Pb (0.177 – 0.545), Cu (0.073 – 0.748), Cd (0.005 – 0.019), Zn (0.264 – 0.915), Cr (0.089 – 0.158), Mn (0.162 – 0.253) and As (0.032 – 0.245) mg/kg. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
2
6
1
Order By: Relevance
“…Malakar et al,(2019), also reported that high arsenic content in irrigation water, accumulates in the top soil (10-15cm) which can change soil quality, consequently altering food quality and human health in the long run. Additionally, increased As level has been found to decrease edible biomass production in beans and the deposition of arsenic in the beans; Mafuyai et al, (2020) worked on health risk assessment of heavy metals in consumption of vegetables irrigated with tin mine pond water in Jos South, Plateau State, reported As concentration of 0.94ppm. Olatoyinbo in 2018 andOgenyi (2018) reported As value to be above the recommended OIGANJI, E; STELLA, D.C; KAHYA, S.S; AHMED, A permissible limits.…”
Section: Arsenicmentioning
confidence: 99%
“…Malakar et al,(2019), also reported that high arsenic content in irrigation water, accumulates in the top soil (10-15cm) which can change soil quality, consequently altering food quality and human health in the long run. Additionally, increased As level has been found to decrease edible biomass production in beans and the deposition of arsenic in the beans; Mafuyai et al, (2020) worked on health risk assessment of heavy metals in consumption of vegetables irrigated with tin mine pond water in Jos South, Plateau State, reported As concentration of 0.94ppm. Olatoyinbo in 2018 andOgenyi (2018) reported As value to be above the recommended OIGANJI, E; STELLA, D.C; KAHYA, S.S; AHMED, A permissible limits.…”
Section: Arsenicmentioning
confidence: 99%
“…Similar by Paluwa et al, 2012 [94] assessed the concentration of Fe and Ni during dry and rainy seasons and noticed that Fe levels reduced by 8.25% in onions and nickel by 45.19% in okro in rainy season samples over those of the dry season, and the mean levels of metals in the okro samples for the dry season were in the order Fe > Cu > Zn > Mn > Ni > Pb > Co > Cr, while those of the rainy season indicated Fe > Cu > Zn > Mn > Ni > Co > Pb > Cr. This trend suggests that okro has a higher retention capacity for essential metals, zinc, manganese, and copper, than for the toxic ones, nickel, lead, cobalt, and chromium (Zhou, et al, 2016) [134] Mafuyai et al 2020a [79] , determined the accumulation of heavy metals in vegetables (garden egg (Solanum melongena), Spinach (Spinacia oleracea L.), Tomato (Lycopersicon esculatum L.), red pepper (Capsicum anum), Carrot (Daucus carota subsp. Sativus) and cabbage (Brassica oleracea) in Jos-South, Plateau State, Nigeria.…”
Section: Reviewsmentioning
confidence: 99%
“…The result revealed that Pb, Cd and Cr were higher than permissible levels in some of vegetables. Similarly, Mafuyai et al 2020b [81] assessed heavy metals concentration in vegetables garden egg (Solanum melongena), Spinach (Spinacia oleracea L.), Tomato (Lycopersicon esculatum L.), red pepper (Capsicum anum), Carrot (Daucus carota subsp. Sativus) and cabbage (Brassica oleracea) irrigated with tin mine pond water in Jos -South, Plateau State and reported that the concentration of the metals was in the range of Pb (0.177 -0.545), Cu (0.073 -0.748), Cd (0.005 -0.019), Zn (0.264 -0.915), Cr (0.089 -0.158), Mn (0.162 -0.253) and As (0.032 -0.245) mg/kg.…”
Section: Reviewsmentioning
confidence: 99%
See 2 more Smart Citations